E-Writing: The Effectiveness of Using Writing Application in Distance Learning - Sari Dewi Noviyanti (Universitas Sembilanbelas November Kolaka, 2021)
The primary aim of this study was to explore the effectiveness of teaching writing skill using E-Writing application in distance learning from the viewpoints of higher education students of Islamic State University of Semarang. Mix method were used as the research design. The quantitative data were obtained through one group pretest posttest design to know the effectiveness of the application to student’s writing achievement. Then, a questionnaire was used to investigate student’s attitude toward the writing application. The results of the writing test showed that student’s writing was improved. The average score of student’s pre-test score was increased for about 27 points, from 59 points to 86 points on post- test. The analysis of student’s questionnaire demonstrated conceptions about using technology of doing independent learning especially in English learning. The study showed that students admit the effectiveness of technology in distance learning and they believe that having learning independency will help them to adapt in any situations